Habilidades sociais, depressão e estresse: um estudo com adolescentes vítimas de abuso sexual - PINHEIRO, Renata Porto (2022)
Findings in the literature indicate that a good repertoire of Social Skills (SH) in children/adolescents may be a protective factor against behavioral problems, as well as a deficient repertoire of SH may be a risk factor. In addition to these data, there are studies relating Sexual Abuse (AS) to depression and stress. In this sense, the general objective of this study was to evaluate how the SS repertoire of adolescent victims of AS is related to the manifestation and intensity of depression and stress, and as specific objectives: (a) to characterize the sample seen at the outpatient clinic specialized to victims of sexual violence at the University Hospital (HU) of São Luís – MA; (b) characterize the SS repertoire, identifying adolescents' deficits and resources; (c) assess the presence and level of depressive symptoms; (d) assess the presence and level of physiological, psychological, cognitive and interpersonal symptoms of stress; (e) relate the variables SH, depression and stress. For this, a descriptive and correlational study was carried out, with 10 female adolescents, aged between 14 and 17 years old, victims of AS, treated at the HU in São Luís - MA. For data collection, the following were used: SINAN form; Participant characterization protocol; Social Skills Inventory for Adolescents - IHSA; Baptist Children's Depression Scale – EBADEP-IJ and Stress Scale for Adolescents-ESA. Data were analyzed following the instrument manuals. Subsequently, descriptive statistical analysis and Spearman correlation were performed. The main results showed a prevalence of rape and multiple forms of violence occurring concomitantly, in adolescents self-declared to be brown, low-income, public school students and with the abuser being within the family or known. Regarding the HS repertoire, five adolescents presented good or elaborate repertoires and five presented deficient repertoires, regarding the level of difficulty in issuing these answers, five adolescents presented low cost and another five, medium or high. Depression patterns were verified in four adolescents, two with mild symptoms and two with moderate symptoms; Stress symptoms were detected in two adolescents, one in the resistance phase and one in the exhaustion phase. A positive correlation was found between assertive SH and depression. Regarding the demographic and social characteristics of the sample, it is possible to affirm that the results are in line with the national literature. Although good and elaborate repertoires of HS were identified in half of the adolescents, high levels of difficulties in emitting these responses were evidenced, which points to the presence of anxiety when emitting them. Depression and stress conditions indicate the need to investigate variables related to AS conditions. The impact of the HS repertoire on depression and stress patterns in AS victims was discussed in the light of Behavior Analysis and the theoretical field of HS. It is concluded that: (1) there is evidence of vulnerability to AS in adolescents with specific social characteristics; (2) Good and elaborate HS repertoires were not sufficient as protective measures; (3) Good and elaborate repertoires of assertiveness were related to depression. The present investigation points to the need for the analysis of the constructs, their impacts and their relationships to consider the victims' life history (ontogenesis) and current conditions, such as AS duration, time of seeking care and antecedent and consequent conditions to the AT. Finally, it is highlighted that AS in female children and adolescents and its psychological effects require researchers to analyze individual contingencies and deepen studies in a macro perspective on the historical construction of the role of women in society. possible through Behavior Analysis and Social Sciences.